A hybrid method for quantifying China's nitrogen footprint during urbanisation from 1990 to 2009. (December 2016) - Cui, Shenghui; Shi, Yalan; Malik, Arunima; Lenzen, Manfred; Gao, Bing; Huang, Wei
Abstract: In this study, we devise a national nitrogen footprint method to evaluate the life cycle nitrogen flows through the national economy of China from 1990 to 2009. To this end, we build a hybrid method based on two well-established techniques, namely material flow analysis (MFA) and input-output analysis (IOA). This integration allows for the evaluation of the effects of international trade and interdependencies among economic sectors. Our results suggest that China's nitrogen footprint (NF) has increased from 30.3 Teragrams (Tg) in 1990 to 54.0 Tg in 2009, whereas the NF per capita has increased from 25.9 to 39.5 kg N/yr. Relationship between the world NF per capita and human development index (HDI) appears to show an inverted U curve, whilst China shows an increase both in NF per capita and HDI. We find that an increase in China's NF is largely associated with high levels of urbanisation. Although the energy NF (E_NF) has increased more drastically than the food NF (F_NF), the latter still dominates China's total NNF, with proportions of 91% in 1990 and 82% in 2009. Taking international trade into account, our results demonstrate that China was a net exporter of F_NF, whilst a net importer of E_NF over this time period. There are many measures considered to reduce China's nitrogen footprint, including improvements in N use efficiency of food systems, transformation of meat-based diets and optimisation of China's economic structure. Highlights: Hybrid method proposed for evaluating nitrogen flows through China's economy. China's nitrogen and food nitrogen footprint quantified from 1990 to 2009. Urbanisation has resulted in an increase in China's nitrogen footprint per capita. Results suggest a drastic increase in China's food nitrogen footprint from 1990 to 2009. Crop production and industrial sectors responsible for a rise in nitrogen footprints